ORGANIZATIONAL COMMUNICATION AND HR SUPERVISION OF PT. WORK PRODUCTIVITY. XYZ IN TANGERANG - Muh Hasan; Rifky Setiawan (Jurnal Comparative: Ekonomi dan Bisnis, 2023)
This study aims to analyze the effect of Organizational Communication and HR Supervision on Work Productivity at T. XYZ. The sample of this research is 60 respondents of employees of T. XYZ with a population of 150. The method used is a quantitative method. Primary data collection was obtained from distributing questionnaires and secondary data obtained from the company. The analytical technique used is multiple linear regression analysis using SPSS software version 22. The results showed that partially the Organizational Communication variable (X1) did not have a positive effect on Work Productivity (Y). This is indicated by tcount > ttable which is 3,501 > 2,2521, HR Supervision (X2) has a positive effect on Work Productivity (Y). This is indicated by tcount > ttable which is 6.428 > 2,2521 and the regression significant value of 0.000 is smaller than 0.05. And simultaneously the variables of Organizational Communication (X1) and HR Supervision (X2) have a positive effect on Work Productivity (Y), namely Fcount > Ftable of 103.262 > 3,15. With multiple regression equation value Y = 2.543+ 0.323X1 + 0.622X2 + e with a coefficient of determination of 39.90%, the rest is influenced by other factors not examined.Keywords: Organizational Communication, HR Supervision, Work Productivity